Efficacy of Adherence-Enhancing Interventions for Immunosuppressive Therapy in Solid Organ Transplant Recipients: A Systematic Review and Meta-Analysis Based on Randomized Controlled Trials - Shi, Yue-Xian; Liu, Chun-Xia; Liu, Fei; Zhang, Hai-Ming; Yu, Ming-Ming; Jin, Yin-Hui; Shang, Shao-Mei; Fu, Ying-Xin (Frontiers in Pharmacology, 2020)
Background: Immunosuppressant non-adherence is a widespread problem among solid organ recipients. With the newly published clinical trials, the randomized controlled trials based systematic review of adherence-enhancing interventions on immunosuppressant adherence in solid organ recipients has not been completed. In this systematic review and meta-analysis, we compared the efficacy of adherence-enhancing interventions versus routine intervention, as performed with RCTs, on immunosuppressant adherence in solid organ transplantation recipients. Methods: PubMed, Embase, Cochrane Library, CINAHL full text, and PsycINFO were searched from database inception to December 2019. This review was conducted following the PRISMA’s reporting guidelines and according to the principles recommended by Cochrane Handbook for Systematic Review. Results: The search yielded 10,479 articles. A total of 27 articles (26 studies) with 715 participants were included in our analysis. Results from the meta-analysis revealed that as compared with that of the routine intervention group, the rates of overall adherence, dosing adherence, and timing adherence were significantly increased within the adherence-enhancing intervention group, with the pooled risk ratio (RR) of overall adherence=1.17, [95% confidence interval (CI): 1.07 to 1.28; p=0.0006]; RR of dosing adherence=1.21 ( 95% CI: 1.08 to1.36, p=0.001); RR of timing adherence=1.16 (95% CI: 1.03 to 1.29, p=0.01). There was a significantly increased adherence score in the adherence-enhancing intervention group; however, no statistical significance on the immunosuppressant blood concentration was found between the two study groups. Results obtained from a subgroup analysis shown interventions led by a multidisciplinary team, both the assessment time at 6 months and 12 months demonstrated a significantly increased adherence rate in the intervention group compared with the control group. Conclusions: The findings of this report indicate that clinicians (doctors and nurses) should maintain a long-term intervention protocol to ensure immunosuppressant adherence within solid organ transplant recipients. To accomplish this goal, we recommend a multidisciplinary team-led, comprehensive intervention approach combined with mobile health monitoring for the administration of an effective immunosuppressive therapy regimen.